Perlindungan Hukum Pekerja Terdampak Pemutusan Hubungan Kerja (PHK) Dalam Masa Pandemi Covid 19 - Krista Yitawati; Anik Triharyani; Yuni Purwati; Krisnaldi Yitnugraha (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2021)
The purpose of this research is to analyze business actors can take care of employment unilaterally during the Covid 19 pandemic period and the form of legal protection for workers affected by employment (PHK) due to Pandemic Covid 19. The method used in this study is a normative legal research method , where this method is used to find the appropriate concrete law to be applied to resolve a particular legal problem, the approach used is the Statute Approach and Conceptual Approach (Conceptual Approach). The results showed that in principle, the company may not carry out layoffs on unilateral workers in any situation, including in the health emergency situation. However, if the layoffs cannot be avoided in public health emergency situations due to the Covid-19 virus pandemic outbreak and still being done by the company, must be with certain reasons. The form of protection for the workforce that is laid off is to provide a practice card, incentives and salary / wages assistance to workers and medical personnel, credit assistance with the restructuring to UMKM, giving THR.